1819 Ind. Acts 39 - (:unkn) unknown (My University, 1819)
An Act to Prohibit the Wearing of Concealed Weapons: Prohibited concealed carry of an dirk, pistol, sword in cane, or any other unlawful weapon. Violators guilty of a misdemeanor, fined not more than one hundred dollars.
Keywords: CARRY - CONCEALED